The Role of Stitch Yarn on the Delamination Resistance in Non-crimp Fabric: Chemical and Physical Interpretation - Shiino, Marcos Yutaka [UNESP]; Pelosi, Tatiane Scarabel [UNESP]; Cioffi, Maria Odila Hilário [UNESP]; Donadon, Mauricio Vicente (Springer Nature, 2017)
In a 3D preform, the out-of-plane reinforcement is effective for decelerating or suppressing the delamination process as the non-crimp fabric does not connect the neighboring laminae effectively. Hence, the interlaminar strength of the stitched laminae is supposed to behave in the same way as a regular unidirectional composite. In order to determine whether or not the stitched yarns contribute to the interlaminar fracture toughness, this study determinated the delamination resistance of a quasi-isotropic laminate. The analysis was based on interlaminar fracture toughness (GIc) and propagation energy curve in tests conducted in mode I opening with double cantilever beam specimen geometry. The results of fracture toughness as well as strain energy for propagation were compared to their fracture surface. A decrease in the propagation energy prevailed in the surface because the stitch yarn replaced the carbon fiber/epoxy interface, which has better chemical affinities, i.e., covalent bonds.
Keywords: composites; failure analysis; mechanical; organic matrix; static; thermal analysis